Predicting Teacher Anxiety, Depression, and Job Satisfaction - Kristen Ferguson; Lorraine Frost; David Hall (University of Windsor, 2012)
This study investigates predictors of anxiety, depression, and job satisfaction in teachers in northern Ontario. Using data from self-report questionnaires, factor analysis and multiple linear regression were performed to determine which sources of stress predict stress-related symptoms among teachers and to explore job satisfaction as predicted by: stress, depression, anxiety, years of teaching experience, gender, grade level assignment and position (part-time vs. full-time). The results indicate that workload and student behaviour were significant predictors of depression in teachers in the study. Workload, student behaviour, and employment conditions were significant predictors of anxiety. In addition, stress and depression had a significant and negative impact on job satisfaction. Years of teaching experience was a significant and positive predictor of job satisfaction. Anxiety, gender, grade level, and position were not statistically significant predictors of teacher job satisfaction. Therefore, efforts made to improve workload, student behavior, and employment conditions may lead to reduced stress among teachers and thus lower levels of depression and anxiety. These results may provide guidance for teachers and administrators, as well as inform teacher retention efforts and attempts to improve teacher job satisfaction.